Influence Of Occupational Safetyand Occupational Health On Employee Performance Of Pt. Laut Timur Utama Durjela Village, Aru Pulau District, Aru Islands Regency - SEMUEL SOUHOKA (Maneggio, 2025)
This research was conducted at PT. Laut Timur Utama, Durjela Village, Pulau-Pulau Aru District, Aru Islands Regency. This study aims to: (1) analyze the effect of Occupational Safety and Health on Employee Performance of PT. Laut Timur Utama, and (2) identify variables that have a dominant influence on Employee Performance. The research method used is quantitative with a sample of 40 respondents. Data analysis includes validity testing, reliability testing, model testing, multiple linear regression analysis, and hypothesis testing with the SPSS program. The results of the regression analysis produce the following equation: Y = 2.587 + 0.336X₁ + 0.411X₂ + e. The results of the study indicate that Occupational Safety and Health has a positive and significant effect on Employee Performance. The Occupational Safety (X₁) and Occupational Health (X₂) variables together contribute 70.3% to Employee Performance (Y), while 29.7% is influenced by other variables not included in this study.